Pengaruh Agama Katolik dalam Pola Relasi Duan-Lolat pada Masyarakat Tanimbar Utara - Umpung, Alfridus Giridus; Oek, Marianus M.; Metintomwat, Matias; Widodo, Agus (Fakultas Teologi, Universitas Sanata Dharma, 2024)
The North Tanimbar community in the Maluku Islands has a tradition of a relationship pattern known as Duan-Lolat (Giver-Receiver). This Duan-Lolat relationship pattern originates from the context of marriage, namely the relationship between man (husband) and woman (wife), which at the same time also implies the relationship between nature and humans (cosmological) as well as the master (the king) with his servants (political). This research, using a qualitative approach with interviews and literature studies, aims to examine the influence of Catholicism in the Duan-Lolat relationship pattern. The results show that before the Catholic faith entered, the people of North Tanimbar embraced animist beliefs centered on human relationships with the universe and ancestral spirits, referred to as Makenar and Batmakenar. After the Catholicism entered in their society, the community’s belief system underwent to change. In this religious context, Duan, as the Giver, which in the original beliefs was identified with men, nature and kings, is now applied to God or Ubila’a, in their language. Meanwhile, Lolat, as the receiver, which was originally identified with women, humans, and servants, is applied to humans in their relationship with God. With this new understanding and meaning, Catholicism can be easily accepted by the North Tanimbar community, while strengthening the community’s understanding of the relationship between humans and God, as well as forming the basis for religious practice and the communityAbstrakMasyarakat Tanimbar Utara di Kepulauan Maluku memiliki tradisi dalam pola relasi yang dikenal dengan Duan-Lolat (Pemberi-Penerima). Pola relasi Duan-Lolat ini berasal dari konteks perkawinan, yaitu relasi antara laki-laki (suami) dan perempuan (istri), yang sekaligus juga berimplikasi konteks relasi alam dengan manusia (kosmologis) dan tuan/raja dengan hamba (politis). Dengan menggunakan pendekatan kualitatif dengan wawancara dan studi pustaka, penelitian ini bertujuan untuk mengkaji pengaruh Agama Katolik dalam pola relasi Duan-Lolat tersebut. Hasilnya menunjukkan bahwa sebelum iman Katolik masuk, masyarakat Tanimbar Utara memiliki kepercayaan animisme yang berpusat pada hubungan manusia dengan alam semesta dan roh-roh leluhur, yang disebut sebagai Makenar dan Batmakenar. Setelah masuknya Agama Katolik, sistem kepercayaan masyarakat mengalami perubahan. Dalam konteks religius ini, Duan, sebagai Pemberi, yang dalam kepercayaan asli diidentikkan dengan laki-laki, alam, dan raja, kini diterapkan pada Allah atau Ubila’a, dalam bahasa mereka. Sementara itu, Lolat, sebagai penerima, yang semula diidentikan pada wanita, manusia, dan hamba, kita diterapkan pada manusia dalam relasinya dengan Allah. Dengan pemahaman dan pemaknaan yang baru ini, Agama Katolik dapat diterima oleh Masyarakat Tanimbar Utara, sekaligus memperkuat pemahaman masyarakat tentang hubungan manusia dengan Allah, serta membentuk landasan praktik keagamaan dan penghayatan spiritual yang mendasari kehidupan beragama di Tanimbar Utara.